Studi Kasus Strategi Komunikasi Pemasaran Pickers Store dalam Meningkatkan Penjualan - Mohammad Fajar Adipratama; Dadan Mulyana (UNISBA Press, 2022)
Abstract. Pickers Store is a store that has a custom concept for street fashion, culture, vintage, retro and do it yourself projects. Pickers Store has been established since 2012. Most of all products and product concepts are always synonymous with automotive, especially classic vehicles. There are various kinds of products such as accessories, clothing, art work, interiors that are shaped into a product. The number of brand businesses out there requires each brand to have a strategy in running its business. This study aims to determine how the pickers store marketing communication strategy in increasing sales. This study uses a qualitative method with a case study approach. The research was conducted in February 2021 to August 2021. The data collected to determine the marketing communication strategy in Pickers Store used interviews and literature studies. In-depth interviews were conducted with the Pickers Store owner and two employees. The results of this study are 1) Pickers Store's marketing strategy focuses on culture related to automotive motorcycle enthusiasts through several activities. 2) The process of designing communication messages is carried out naturally but still systematically and planned. 3) Social Media Instagram has become a very influential digital platform in Pickers Store marketing activities. Abstrak. Pickers Store merupakan salah satu toko yang mempunyai konsep custom street fashion, culture, vintage, retro and do it yourself project. Pickers Store telah berdiri sejak tahun 2012. Dari sebagian besar seluruh produk dan konsep produk selalu identik dengan automotive, khususnya kendaraan klasik. Adapaun berbagai macam produk seperti accessories, clothing, art work, interior yang dibentuk menjadi suatu produk. Banyaknya usaha brand di luar sana menuntut setiap brand mempunyai strategi dalam menjalankan usahanya. Penelitian ini bertujuan untuk mengetahui bagaimana strategi komunikasi pemasaran Pickers Store dalam meningkatkan penjualannya. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Penelitian dilaksanakan pada bulan Februari 2021 sampai desember 2021. Data yang dikumpulkan guna mengetahui strategi komunikasi pemasaran dalam pickers store menggunakan wawancara dan observasi. Wawancara dilakukan secara mendalam kepada pemilik Picker Store dan Admin Media Sosial Pickers Store. Hasil dari penelitian ini adalah 1) Strategi pemasaran Pickers Store berfokus pada culture yang berhubungan dengan automotive penyuka motor melalui beberapa kegiatan. 2) Proses merancang pesan komunikasi dilakukan secara natural tetapi tetap sistematis dan terencana. 3) Media Sosial Instagram menjadi platform digital yang sangat berpengaruh dalam kegiatan pemasaran Pickers Store.